2016
DOI: 10.1242/jcs.181883
|View full text |Cite
|
Sign up to set email alerts
|

Activator of G-protein signaling 8 is involved in VEGF-mediated signal processing during angiogenesis

Abstract: Activator of G-protein signaling 8 (AGS8) is a receptor-independent accessory protein for the Gβγ subunit, which was isolated from the rat heart subjected to repetitive transient ischemia with the substantial development of collaterals. Here, we report the role of AGS8 in vessel formation by endothelial cells. Knockdown of AGS8 by small interfering RNA (siRNA) inhibited VEGF-induced tube formation, as well as VEGF-stimulated cell growth and migration. VEGF stimulated the phosphorylation of the VEGF receptor-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 40 publications
(61 reference statements)
2
30
0
Order By: Relevance
“…Interestingly, intravitreal AGS8 siRNA injections significantly inhibited CNV formation and the vascular budding area of the RPE-choroid complex. These findings complemented the in vitro study, which showed that the molecular mechanism of angiogenesis is mediated by AGS8 15 and demonstrated the regulation of angiogenesis in vivo by accessory proteins for G-protein. Our data also suggest the potential of AGS8 as a therapeutic target to control neovascularization in human diseases.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Interestingly, intravitreal AGS8 siRNA injections significantly inhibited CNV formation and the vascular budding area of the RPE-choroid complex. These findings complemented the in vitro study, which showed that the molecular mechanism of angiogenesis is mediated by AGS8 15 and demonstrated the regulation of angiogenesis in vivo by accessory proteins for G-protein. Our data also suggest the potential of AGS8 as a therapeutic target to control neovascularization in human diseases.…”
Section: Discussionsupporting
confidence: 76%
“…The effect of AGS8 knockdown on VEGFR-2 signal is associated with a decrease of cell surface expression of VEGFRs 15,16 . Therefore, we analyzed the cell surface expression of VEGFR-2 in RF/6A cells using FACS analysis with an FITC-conjugated anti-VEGFR-2 antibody.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Wnt signaling pathway positively regulates osteogenesis in BMMSC and ALP and runt-related transcription factor 2 (Runx2), which are the representative factors in the downstream of osteogenesis-angiogenesis [ 5 7 ]. Mitogen-activated protein kinase (MAPK) signaling pathway positively regulates angiogenesis by targeting VEGF expression [ 8 10 ]. However, exogenous osteogenetic and angiogenic stimulants would cause imbalance of bone formation, leading to excessive bone formation or vascular leakage at the risk of tumorigenesis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%